Characterizing physical properties and morphological structures of peroxidevulcanized and sulphur-vulcanized natural rubber latex films / Roslim Ramli - Ramli, Roslim (2015)
The characteristics of the morphological structure of natural rubber latex films prepared from both sulphur and peroxide vulcanization process are visualized under the transmission electron microscope. In sulphur-vulcanized natural rubber latex films, the crosslinked regions appeared as dark areas within the elliptical shaped rubber particles and as strands around the rubber particles section in between rubber particles linking the rubber particles. In peroxide-vulcanized natural rubber latex films, crosslinks region appeared denser at the outer surface of the rubber particles compared to the inner phase.Hydroxyacetone has been shown as an effective activator for tert-buthyl hydroperoxide in the prevulcanization of natural rubber latex using peroxide process. The maximum tensile strength value was observed to occur at film prepared at a prevulcanization temperature of 60 °C, heating for 3 hours. The drying time and temperature play an important role in controlling the strength property of peroxide-vulcanized natural rubber latex films.Crosslink density is not the only factor that contributes to high strength property of natural rubber latex films.The addition of higher levels of crosslinking agent resulting in higher crosslink density and modulus of elasticity values, but, too high crosslinking may lead to subsequent decreased in the tensile strength value. Thus, a combination of the right degree of crosslinking range and the degree of particle cohesion are important factors governing the strength of natural rubber latex films. Leaching treatment and drying at elevated temperature, improved the coalescence of the rubber particles which in turn improved the tensile strength of the films. The addition of antioxidant hinders the thermal-oxidative effect during the drying process and thus, greater coherence of the films by heat treatment could be obtained.